A novel method for isolation new strain of E. coli ( resist for Ampicillin and sensitive for Gentamycin ) and other (sensitive for Ampicillin and resist for Gentamycin )and check it’s conjugation by solid media , liquid media and it’s stability by serial - et.al, Mohammed Abdul Rahmman Mohammed (Al-Qadisiyah Journal of Pure Science, 2017)
Bacterial strains ( E. coli ) were collected from two different places , The first strain was collected from central Laboratory â€“ Baghdad university , meanwhile the second strain was collected from pathogenic laboratory â€“ Baghdad university Replica plating and gradient plate method technique were used to prepare strains with different multi trails Replica plating was used to select strain resist to specific antibiotic with low concentration ( sensitive for other type of antibiotic ) then go head subsequently with gradient plate method to adapt the strain to resist (high concentration ) Replica plating was used to select first strain resist to Amp. ( 100 Mg / ml ) and ( sensitive to Gen.) then gradient plate method was used to adapt first strain to resist Amp. (500 Mg-ml ) therefore. first strain was resistant to Amp. ( 500 Mg / ml ) and sensitive to Gen. (500 Mg / ml ) , on other hand ,by using same methods , second strain was resistant to Gen. ( 500 Mg / ml ) and sensitive to Amp.. (500 Mg / ml ) To visualize if ( Amp. resist trail and Gen. resist trail ) carried on plasmid , first and second strains were conjugated by using conjugation technique in solid media and liquid media . The conjugant strain was resistant to ( 1000 Mg / ml ) by which it resists Amp. and Gen. , (500 Mg / ml ) for each antibiotic . The efficiency of conjugant was determined on solid media and liquid media , it was so high a round 9% . The conjugant strain was checked for stability of it’s plasmid by using sub â€“ culturing method . It was stable for 25 times of sub-culturing Concentration of the protein for E. coli ( resist for Ampicillin and sensitive for Gentamycin ) and other strain E. coli (sensitive for Ampicillin and resist for Gentamycin ) was 0.0021and 0.0052 meanwhile conjugant was 0.106Finally , . using replica plating , gradient plate and conjugation process consider as a novel technique to prepare strains with multi trails which resist very high concentration of antibiotics and efficient conjugation process